Mixed matrix membrane and its preparation method and application

By using the microwave method synthesized TpTta-COF nanorods as fillers in the mixed matrix membrane, combined with the PIM-1 matrix, an excellent PIM-1/TpTta-COF hybrid matrix membrane was prepared, which solved the shortcomings of the existing membranes in CO2 separation performance and industrial applications, and achieved efficient gas separation and stable performance.

CN116236915BActive Publication Date: 2025-04-22CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310032021.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-04-22
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

The existing hybrid matrix membranes have shortcomings in CO2 separation performance and industrial application value, especially the filler size, dispersion and interface compatibility issues limit their performance.

Method used

The polymer PIM-1 is used as the matrix, and the covalent frame polymer TpTta-COF nanorods connected with β-ketoenamine were synthesized as fillers by microwave method, and the PIM-1/TpTta-COF mixed matrix membrane was prepared by solution casting and evaporation method to achieve rapid and simple preparation and microenvironment regulation.

Benefits of technology

It improves the gas separation performance, significantly exceeds the Robeson upper limit, significantly improves the selectivity and permeability of CO2/N2 and CO2/CH4, and improves the stability and industrial application value of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116236915B_ABST
    Figure CN116236915B_ABST
Patent Text Reader

Abstract

The invention discloses a mixed matrix membrane and a preparation method and application thereof, comprising the following steps: providing an intrinsic microporous polymer PIM-1; subjecting 1,3,5-trialdehyde phloroglucinol and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to microwave reaction in the presence of a catalyst to prepare a covalent framework polymer TpTta-COF having a β-ketoenamine structure; dispersing PIM-1 and TpTta-COF in a solution, and preparing a PIM-1 / TpTta-COF mixed matrix membrane by a solution casting evaporation method. The present invention adopts a microwave method to quickly and easily prepare a TpTta-COF nanorod filler with a small size and a high specific surface area, which is mixed with PIM-1 to form a film, and is easy to realize industrialization. The COFs morphology control characteristics connected by β-ketoenamine and the strong hydrogen bonding between the COFs and the polymer PIM-1 are used to improve the compatibility between the matrix and the filler, which significantly improves the gas (CO 2 )Separation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a mixed matrix membrane and a preparation method and application thereof. Background Art

[0002] Mixed matrix membranes (MMMs) are membranes made by uniformly dispersing fillers in a polymer matrix, which combines the advantages of both polymer matrix and filler particles.

[0003] Intrinsic microporous polymers (PIMs) as polymer matrices have high specific surface area and high free volume, high permeability and general selectivity, and their good film-forming properties make them feasible in the field of CO2 membrane separation. Among them, PIM-1 is the most studied one, but its overall CO2 separation performance is still below the 2008 Robeson upper limit (the trade-off between gas permeability and selectivity). In order to surpass the Robeson upper limit, researchers have explored various strategies, such as chemical post-modification or physical mixing.

[0004] Known MMMs fillers include graphene oxide (GO), metal organic frameworks (MOFs), covalent framework polymers (COFs), etc. COFs are long-range ordered crystalline polymers whose geometric structure retention and porosity can be precisely adjusted through organic synthesis. Compared with other inorganic porous fillers, COFs are completely organic in nature and have the unique advantage of good compatibility with polymer matrices. Although COFs-based MMMs have made significant progress, their performance is still limited by filler size, filler dispersion and poor interface compatibility between fillers and matrix. For example, COF fillers obtained by the flame sealing method are often large and difficult to disperse irregular particles due to strong pi-pi interactions. In addition, the synthesis of COF often requires harsh reaction conditions, such as anhydrous and oxygen-free, flame sealing and long time (3-6 days), which greatly reduces its practical application value. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and provide a mixed matrix membrane and its preparation method and application, which can achieve rapid and easy preparation while precisely controlling the microenvironment such as membrane pores and surface, thereby improving gas separation performance and industrial application value.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A method for preparing a mixed matrix membrane comprises the following steps:

[0008] (1) Providing an intrinsic microporous polymer PIM-1;

[0009] (2) subjecting 1,3,5-trialdehyde phloroglucinol and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to a microwave reaction in the presence of a catalyst to prepare a covalent framework polymer TpTta-COF having a β-ketoenamine structure;

[0010] (3) PIM-1 and TpTta-COF were dispersed in a solution, and a PIM-1 / TpTta-COF mixed matrix membrane was prepared using a solution casting evaporation method with PIM-1 as the matrix and TpTta-COF as the loaded filler.

[0011] Furthermore, in step (2), the molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is (0.95-1.05):1.

[0012] Furthermore, the catalyst in step (2) is HOAc, and the molar ratio of HOAc to 1,3,5-trialdehyde phloroglucinol is (20-25):1.

[0013] Furthermore, in step (2), the microwave reaction temperature is 80-150° C., the frequency is 10-100 GHz, and the reaction time is 10-30 min.

[0014] Furthermore, the TpTta-COF prepared in step (2) is a nanorod with a diameter less than 30 nm and a length not exceeding 200 nm, and is a crystalline material having a periodic hexagonal framework.

[0015] Furthermore, the content of TpTta-COF in the PIM-1 / TpTta-COF mixed matrix membrane in step (3) is 2-8%.

[0016] The invention also provides a mixed matrix membrane, which is prepared by adopting the method.

[0017] The invention also provides an application of the mixed matrix membrane in gas separation.

[0018] The present invention uses polymer PIM-1 as a matrix and TpTta-COF nanorods (COFs connected by β-ketoenamine) as fillers, and prepares a PIM-1 / TpTta-COF mixed matrix membrane by physical blending. Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention adopts microwave synthesis to quickly and easily prepare mixed matrix membrane COF filler: TpTta-COF nanorods, which is easy to industrialize. In addition, the prepared nanorods are small in size (diameter less than 30nm, length not exceeding 200nm), high in specific surface area, and controllable in morphology, making it easier to disperse and prepare mixed matrix membranes.

[0020] (2) The TpTta-COF filler prepared by the present invention has the characteristics of high specific surface area, regular shape, small size and rich porosity, and has excellent affinity for CO2. The high specific surface area and regular pores of the filler itself provide active sites and transmission channels for CO2 transmission, thereby improving the gas separation performance of the membrane material.

[0021] (3) At the same time, the present invention utilizes the strong hydrogen bonding between the COFs linked by β-ketoenamine and the polymer PIM-1 to improve the compatibility between the matrix and the filler.

[0022] The TpTta-COF nanoparticles with high CO2 adsorption capacity are uniformly distributed in the matrix, forming a fast and continuous CO2 transmission channel, and strengthening the interfacial compatibility with the matrix PIM-1 through hydrogen bonding, thereby avoiding the formation of interfacial defects and retaining the original gas transmission channel. Therefore, the addition of β-ketoenamine-linked COFs significantly improves the permeability and selectivity of MMMs based on polymer PIM-1, showing excellent gas (CO2) separation performance and successfully surpassing the Robeson upper limit (2008) of gas pairs CO2 / N2 and CO2 / CH4.

[0023] Furthermore, the MMMs prepared in the present invention show excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 a) IR spectrum, b) SEM image, c) thermogravimetric curve, d) X-ray diffraction pattern and simulation image of TpTta-COF;

[0026] Figure 2 a) N2 adsorption / desorption isotherms of TpTta-COF at 77K (the inset is the pore size distribution), b) CO2 and N2 adsorption isotherms of TpTta-COF at 273K and 298K, c) isosteric adsorption lines of CO2 and N2 on TpTta-COF, d) isosteric adsorption heats of CO2 and N2 on TpTta-COF;

[0027] Figure 3 are the optical images of PIM-1 / TpTta-COF MMMs with different loading amounts;

[0028] Figure 4 are ATR-FTIR spectra of a) pure PIM-1 membrane and PIM-1 / TpTta-COF MMMs, b) ATR-FTIR spectra of pure PIM-1, TpTta-COF, and 1:1 PIM-1 / TpTta-COF;

[0029] Figure 5 are surface SEM images: a) PIM-1 membrane, b) PIM-1 / TpTta-COF-2wt%, c) PIM-1 / TpTta-COF-4wt%, d) PIM-1 / TpTta-COF-6wt%, e) PIM-1 / TpTta-COF-8wt%, cross-sectional views: f) PIM-1 membrane, g) PIM-1 / TpTta-COF-2wt%, h) PIM-1 / TpTta-COF-4wt%, i) PIM-1 / TpTta-COF-6wt%, j) PIM-1 / TpTta-COF-8wt% (inset: magnified image);

[0030] Figure 6 a,f) pure PIM-1 membrane, b,g) PIM-1 / TpTta-COF 2wt%, c,h) PIM-1 / TpTta-COF 4wt%, d,i) PIM-1 / TpTta-COF 6wt%, e,j) PIM-1 / TpTta-COF 8wt% membrane surface AFM images (scanning range: 10×10μm (3D) and 5×5μm (2D));

[0031] Figure 7 Contact angles of a) TpTta-COF, b) PIM-1, c) PIM-1 / TpTta-COF 2wt%, d) PIM-1 / TpTta-COF 4wt%, e) PIM-1 / TpTta-COF 6wt%, f) PIM-1 / TpTta-COF 8wt%;

[0032] Figure 8 a) Thermogravimetric curve and b) DTG curve of PIM-1 / TpTta-COF MMMs;

[0033] Fig. 9 is the XRD spectrum of PIM-1 / TpTta-COF MMMs;

[0034] Fig.10Effect of filler TpTta-COF loading on a) gas permeation performance, b) selectivity, c) permeability, d) permeation performance test of PIM-1 / TpTta-COF 6 wt % MMMs for 72 h. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0038] Test instruments and methods :

[0039] TpTta-COF and PIM-1 / TpTta-COF MMMs were characterized by FTIR spectroscopy (ATR-FTIR, Nicolet iS50, America) with a scanning range of 4000–500 cm -1 . Using liquid on Bruker-Advance 600 1H NMR spectroscopy was used to characterize the structures of the corresponding substances. X-ray diffraction (XRD) patterns were collected using a Bruker Advanced D8 diffractometer with a step size of 0.02° and a scanning range of 2° to 30°. The thermogravimetric analysis (TGA) produced by Mettler Toledo, Switzerland, was used in the range of 30 to 800°C with a heating rate of 10°C / min in a N2 atmosphere to obtain the thermogravimetric data of TpTta-COF and PIM-1 / TpTta-COF MMMs. The molecular weight of PIM-1 was obtained by gel permeation chromatography at room temperature using tetrahydrofuran as the mobile phase at a flow rate of 1 mL / min. The nitrogen adsorption and desorption isotherms and pore size distribution curves of the porous materials were measured at 77 K using ASAP 2020 C (Micromeritics Instrument Corporation, America). All samples were first degassed at 100°C under high vacuum for 10 h. The pore size distribution was calculated using the nonlocal density functional theory (NL-DFT) method. Atomic force microscopy (AFM) was used to study the surface roughness and micromorphology of the membrane. Scanning electron microscopy (SEM, FEI SIRION200, America) was used to observe the micromorphology of TpTta-COF and PIM-1 / TpTta-COF MMMs samples. The mole fraction of the mixed gas on the feed side and the permeate side was determined by gas chromatograph (Agilent GC 8860) during the membrane performance test.

[0040] The membrane performance test method is as follows: all gas permeabilities and selectivities are measured by constant pressure method on the gas permeometer using Wicke-Kallenbach technology. In order to calibrate the preset feed side gas flow rate, a mass flow controller calibrated by a manual bubble flowmeter is used. After the entire set of measuring instruments reaches a stable state, the permeated gas is detected using an online calibrated Agilent 8860 gas chromatograph. The feed side pressure of the membrane is maintained at 0.30 MPa, and the measurement is carried out at room temperature. The effective area of ​​the membrane is approximately 12.56 cm 2 The gas permeabilities and selectivities under steady-state conditions were recorded and the average of at least three observations was used to ensure numerical accuracy.

[0041] Example: Preparation and characterization of PIM-1 / TpTta-COF mixed matrix membrane

[0042] 1. Synthesis of polymer PIM-1

[0043] At room temperature, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane (6.00g, 17.63mmol), tetrafluoroterephthalonitrile (3.53g, 17.63mmol) and anhydrous N,N-dimethylformamide (120mL) were added to a dry three-necked flask in sequence. It became clear under magnetic stirring, and then anhydrous K2CO3 (7.32g, 52.88mmol) was slowly added under a nitrogen atmosphere, and finally the temperature was gradually raised to 65°C for 72h. After the reaction was completed, it was cooled to room temperature, and the reaction solution was slowly poured into deionized water (600mL) to precipitate a yellow solid, which was collected by vacuum filtration to obtain a crude product. The crude product was dissolved with a small amount of chloroform and then precipitated in excess methanol. The above process was repeated three times. Finally, the product precipitated in methanol was filtered under reduced pressure, and the filter cake was collected. The filter cake was vacuum dried at 60° C. overnight to obtain a bright yellow solid, which was the polymer PIM-1, with a yield of 85%.

[0044] The molecular weight test of PIM-1 by gel permeation chromatography (GPC) showed that the number average molecular weight (Mn) was 50090 g / mol, the weight average molecular weight (Mw) was 82175 g / mol, and the polydispersity was Mw / Mn=1.64, which reflects that the synthesized PIM-1 has a high degree of reaction, which is conducive to the preparation of membranes with good mechanical properties.

[0045] 2. Microwave Synthesis of Polymer TpTta-COF

[0046] At room temperature, 1,3,5-trialdehyde phloroglucinol (0.2mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (0.2mmol) were added to the autoclave. Then 1,4-dioxane (9.2mL) and mesitylene (0.92mL) were added thereto, and then ultrasonic treatment was performed for 10min to form a uniformly dispersed reaction solution. After the ultrasonic treatment was completed, the reaction mixture was transferred to the autoclave and freshly prepared HOAc (6M, 0.72mL) was added. Then the reaction mixture was transferred to a microwave reactor and microwave reaction (frequency of 10-100GHz) was performed at 120°C for about 20min. After cooling to room temperature, the product was collected by vacuum filtration, and the filter cake was washed with tetrahydrofuran, ethanol and acetone in turn to obtain an orange-yellow powder with a yield of 88.6%.

[0047] The synthetic route is as follows:

[0048]

[0049] Figure 1 -a is the infrared spectra of the monomers trialdehyde pyrogallol (Tp), 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (Tta) and filler TpTta-COF. The comparison shows that a covalent framework polymer with a β-ketoenamine structure is formed.

[0050] like Figure 1 -b, the microscopic morphology of TpTta-COF material was observed by scanning electron microscopy. The obtained TpTta-COF has a certain agglomeration phenomenon, but the particle size and shape of the material can still be clearly observed. The average particle size of the material is about 143nm (length) and 25nm (diameter), and the shape is nanorod-like.

[0051] like Figure 1 -c shows that TpTta-COF was subjected to thermogravimetric analysis. The material's 5% thermal weight loss temperature is as high as 316°C. The filler TpTta-COF has excellent thermal stability, with a residual content of more than 45% at 800°C.

[0052] like Figure 1 -d, the X-ray diffraction spectrum of TpTta-COF shows that it is a highly crystalline material with a periodic hexagonal framework. The 2θ value of the first intensity peak is 5.9°, which is consistent with the diffraction spectrum simulated using the overlapping superposition model and the experimental diffraction spectrum.

[0053] The porous structure of filler TpTta-COF was investigated by N2 adsorption and desorption at 77K. Figure 2 As shown in a. The filler TpTta-COF has a large number of microporous structures. According to the BET multilayer adsorption theory calculation, the BET specific surface area of ​​TpTta-COF is 1054m 2 / g, which is higher than the data reported in previous literature. At the same time, the NL-DFT method was used to calculate that the pore size distribution is mainly concentrated at 1.061nm ( Figure 2 a). It can be seen that TpTta-COF is a type of microporous material with high specific surface area and relatively concentrated pore size distribution. Figure 2 As shown in Figure b, the CO2 and N2 adsorption isotherms of TpTta-COF at 273K and 298K are depicted. At 273K and 1 bar, the adsorption capacity of TpTta-COF for CO2 is 67.18 cm 3 / g, compared with 10.79 cm2 adsorption of N2. 3 / g; at 298K and 1 bar, the adsorption capacity of CO2 by TpTta-COF is 41.33 cm 3 / g, while the adsorption capacity of N2 is 8.99cm 3 / g. This indicates that TpTta-COF has an excellent affinity for CO2. In addition, in order to verify that TpTta-COF has an excellent affinity for CO2, the isosteric adsorption heat (Qst) of TpTta-COF was calculated using the Clausius-Clapeyron equation based on the two-position Langmuir model method of the adsorption isotherms at 273K and 298K ( Figure 2 c, d). In the extremely low adsorption range, the isosteric adsorption heats of CO2 and N2 of TpTta-COF are calculated to be 28-40.3 kJ / mol and 8.5-22.1 kJ / mol, respectively. The Qst value of CO2 is significantly higher than that of N2. This significant difference is caused by the abundance of basic nitrogen, which strongly interacts with acidic CO2 molecules. Based on the above conclusions, the material TpTta-COF can effectively separate CO2 and N2, meeting the selection criteria of fillers.

[0054] 3. Preparation of PIM-1 / TpTta-COF Mixed Matrix Membranes

[0055] The gas separation membrane is prepared by solution casting evaporation method. The mass fraction of filler added to the mixed solution is defined by the following formula.

[0056]

[0057] In order to study the effect of organic filler TpTta-COF in MMMs, five membranes with different filler contents (0, 2, 4, 6 and 8 wt%) were fabricated. First, the weighed TpTta-COF was ultrasonically dispersed in CHCl3 for 1 h to obtain a uniformly dispersed suspension. The weighed PIM-1 was stirred in CHCl3; then the TpTta-COF suspension was added to the PIM-1 solution, and the mixture was magnetically stirred for 24 h to obtain a uniformly dispersed PIM-1 / TpTta-COF membrane. The membrane solution was then transferred to an ultra-flat culture dish, and the solvent was evaporated at room temperature to form a mixed matrix membrane. The obtained membrane was vacuum dried at 50°C, and the membrane thickness was measured by digital micrometer and cross-sectional scanning electron microscopy, which was about 60-80 μm.

[0058] Figure 3 The optical images of the mixed matrix films show that the surfaces of these films are smooth and evenly distributed with uniform color distribution, and there are no visible cracks or filler aggregation. The films were observed using backlighting, and it was found that these films did not have pores left by solvent evaporation or interface defects caused by compatibility issues between fillers and the matrix.

[0059] Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) was used to characterize the PIM-1 / TpTta-COF mixed matrix membrane. Figure 4-a, with the increase of TpTta-COF loading, the intensities of aromatic C=C and Ar-O-Ar peaks increase, which is due to the overlap of the absorption peaks of the triazine ring in the filler TpTta-COF, and also indicates that the filler TpTta-COF is successfully introduced into the PIM-1 matrix. Figure 4 As shown in Figure 2, in the ATR-FTIR spectrum of PIM-1 / TpTta-COF, when the mass fraction of TpTta-COF was 50%, it was clearly observed that the -1 and 1285cm -1 It was found that the infrared absorption band shifted to a lower frequency and the signal intensity decreased accordingly, which indicated that there was an obvious hydrogen bonding between the -NH group in TpTta-COF and the -C≡N in PIM-1.

[0060] Scanning electron microscopy (SEM) was used to analyze the surface, cross-sectional morphology, and microstructure of pure PIM-1 membranes and PIM-1 / TpTta-COF MMMs, e.g. Figure 5 As shown in the figure, with the increase of the loading amount of filler TpTta-COF (a-e), the membrane surface gradually changed from uniform and smooth to inconsistent and rough. However, no visible voids or defects were observed, indicating good compatibility between the filler TpTta-COF and the PIM-1 matrix. At the same time, the cross-sectional SEM images of the MMMs further verified the dispersion state of TpTta-COF in the matrix (f-j). Compared with the continuous, smooth and dense PIM-1 membrane (f), the MMMs with different TpTta-COF loadings showed many nanoparticles in the cross section (g-j). In addition, the morphology of the polymer matrix also changed, forming a structure with wrinkles and polymer veins. The strong interaction between the polymer matrix and the filler has been shown to promote the generation of these features during the fracture process. This excellent particle-polymer interaction benefits from the hydrogen bonding between the -NH groups in TpTta-COF and the -C≡N in PIM-1. It can also be observed that the addition of filler TpTta-COF enables the formation of a network structure that runs through the continuous film in the PIM-1 matrix.

[0061] Atomic force microscopy (AFM) was used to analyze the effect of the addition of filler TpTta-COF on the surface roughness of the membrane. Figure 6As shown. The scanning area is 10×10μm (3D) and 5×5μm (2D). The bright spots and dark spots in the photo represent the top surfaces of the high points and valleys of the film, respectively. Ra and Rq are usually used to evaluate surface roughness (Table 1). It can be found that the root mean square roughness (Rq) values ​​of PIM-1, PIM-1 / TpTta-COF 2wt%, PIM-1 / TpTta-COF 4wt%, PIM-1 / TpTta-COF 6wt%, and PIM-1 / TpTta-COF8wt% are 4.16nm, 13.9nm, 21.1nm, 31.7nm, and 34.3nm, respectively. The surface roughness of the MMMs film gradually increases with the addition of filler TpTta-COF. The increase in the surface roughness of the film is mainly due to hydrogen bonds and electrostatic interactions between polymer chains and between the polymer matrix and the filler.

[0062] Table 1 Surface roughness parameters of pure PIM-1 membrane and PIM-1 / TpTta-COFMMMs membrane

[0063]

[0064] The contact angle is used to test whether the surface characteristics of the membrane are hydrophilic or hydrophobic. Hydrophobic membranes are conducive to the passage of gases. Figure 7 As shown in the figure, the filler TpTta-COF, the polymer matrix PIM-1 and the PIM-1 / TpTta-COF MMMs with different filler loadings were characterized. The results show that the contact angles of the filler TpTta-COF and the matrix PIM-1 are 67.6° and 84.6°, respectively. The contact angle of pure PIM-1 is slightly less than 90°, indicating that PIM-1 is slightly hydrophilic, which is not conducive to the contact between the gas and the membrane surface. However, when the two are physically blended to form a mixed matrix membrane, the contact angle increases and the contact angle exceeds 90° to become a hydrophobic membrane. The main reason is that the filler is evenly dispersed in the membrane and wrapped by the polymer matrix PIM-1. At the same time, those N and O heteroatoms are used to form hydrogen bonds with the matrix, which reduces the hydrophilic groups of the filler and the matrix and the contact surface with water, thereby turning the mixed matrix membrane into a hydrophobic membrane. The hydrophobic membrane can better allow gas contact, which also confirms that the hydrogen bond interaction between the filler and the matrix promotes the interfacial compatibility between the filler and the matrix.

[0065] Thermogravimetric analysis (TGA) and differential thermogravimetric (DTG) analysis were used to characterize the MMMs with different TpTta-COF loadings, such as Figure 8As shown. When the TpTta-COF loading is 2-6wt%, the thermal stability of the PIM-1 membrane is improved. In contrast, the addition of TpTta-COF to the PIM-1 matrix can improve the thermal stability of TpTta-COF due to the additional 4wt% weight loss caused by the decomposition of TpTta-COF at 800°C, which is attributed to the hydrogen bonding between the -NH groups in TpTta-COF and the -C≡N in PIM-1. And when the MMMs are heated to 800°C, there is still a residual amount of more than 60%, which shows that the prepared MMMs have good thermal stability and can meet the thermal stability requirements of the membrane when used as a gas separation membrane.

[0066] X-ray diffraction (XRD) was used to characterize the MMMs with different TpTta-COF loadings, such as Fig. 9 As shown. Further XRD analysis revealed the amorphous nature of the pure PIM-1 membrane, and two characteristic peaks were observed at 2θ = 12.8° and 2θ = 18.1°. The characteristic peak at 12.8° was mainly formed due to the loose twisted main chain stacking, while the broad peak at 18.1° was formed due to the effective stacking between polymer chains. With the addition of filler TpTta-COF particles, a new characteristic peak appeared at 2θ = 5.9°, and the peak intensity increased with the increase of TpTta-COF loading. This indicates that the crystal structure of the added TpTta-COF was not destroyed, and the original pores of TpTta-COF and PIM-1 were not blocked during the preparation of MMMs.

[0067] In summary, the addition of filler TpTta-COF can effectively overcome the blockage of the original gas transmission channel between the filler and the matrix and meet the needs of practical applications.

[0068] Performance test: PIM-1 / TpTta-COF MMMs gas separation performance

[0069] In order to study the gas separation performance of the prepared membrane, CO2 / N2 and CO2 / CH4 mixed gases (volume ratio of 50mL:50mL) were used as test gases. The separation performance results are shown in Fig.10 a~c are shown. The permeability of all prepared membranes is in the following order: CO2>CH4>N2. This trend is similar to that of most polymer membranes, which follow the solubility selection mechanism of gas permeation. CO2 has the highest permeability due to its higher critical temperature [CO2(304.2K)>CH4(190.6K)>N2(126.2K)] and the affinity of the membrane for it. Although the kinetic diameter of CH4 is larger than that of N2 and CO2 (the kinetic diameters of CO2, N2 and CH4 are and ), but the permeability of CH4 is greater than that of N2, which is mainly because membrane separation mainly uses the dissolution-diffusion mechanism. Based on this mechanism, the higher condensation temperature of CH4 can increase its solubility compared with N2. Although the diffusion is lower, the permeability of CH4 is higher than that of N2, so the selectivity of CO2 / N2 is higher than that of CO2 / CH4. Compared with pure PIM-1 membrane, PIM-1 / TpTta-COF MMMs prepared by adding filler TpTta-COF improve the permeability of CO2 ( Fig.10 a). The permeation flux of CO2 increases with the increase of TpTta-COF loading (2-6wt%). When the loading of TpTta-COF is 6%, MMMs have the best separation performance, and the CO2 permeation flux of PIM-1 / TpTta-COF MMMs increases from 4018 Barrer of PIM-1 to 9534 Barrer. At the same time, compared with the pure PIM-1 membrane, the selectivity of PIM-1 / TpTta-COF MMMs for CO2 / N2 is also greatly improved, from 17.4 to 26.3 ( Fig.10 b). Fig.10 c shows that the CO2 permeability increases with the increase of TpTta-COF loading (2-6 wt%). When the TpTta-COF loading is 6%, the CO2 permeability of MMMs increases from 86 GPU of PIM-1 to 125 GPU (gas permeability unit: 1 GPU = 3.335 × 10 -10 mol m -2 s -1 Pa -1at STP). This result is mainly attributed to the addition of CO2-philic TpTta-COF nanoparticles. The filler TpTta-COF has a high CO2 adsorption capacity and can preferentially adsorb CO2 molecules so that they can be transported through the pores of the filler, thereby promoting the transport of CO2. The excellent adsorption capacity comes from the rich basic heteroatoms N of the TpTta-COF nanoparticles, which can enhance the interaction with CO2 molecules through dipole-dipole interactions. In addition, based on the gas test results, it is shown that this may be due to the good compatibility between the polymer matrix and the filler TpTta-COF nanoparticles, because the polymer matrix PIM-1 can form hydrogen bonds and π-π stacking with the filler TpTta-COF, effectively avoiding the interface defect problem between the filler and the matrix, thereby increasing the permeation flux and selectivity of MMMs. At the same time, after adding TpTta-COF nanoparticles to the polymer PIM-1 matrix, a continuous network structure is formed, which can provide a fast channel for gas to pass through the membrane, so that the MMMs have high permeability and selectivity. For PIM-1 / TpTta-COF MMMs, when the TpTta-COF nanoparticle loading increased to 8wt%, the TpTta-COF particles agglomerated significantly (as can be clearly seen from the SEM image), resulting in the formation of non-selective voids between the filler and the polymer matrix. These non-selective voids can provide additional transmission channels for N2 and CH4. As a result, the N2 and CH4 permeation fluxes increased accordingly, while the CO2 / N2 and CO2 / CH4 separation selectivities decreased accordingly. In general, when TpTta-COF nanoparticles were used as fillers, the CO2 / N2 and CO2 / CH4 selectivities and CO2 permeabilities of the modified mixed matrix membranes were significantly improved compared to the pure PIM-1 membrane. In particular, when the filler TpTta-COF loading was 6wt%, the CO2 permeation flux increased by 137% and the CO2 / N2 selectivity increased by 51%.

[0070] Compared with the gas separation performance of pure PIM-1, the gas separation performance of PIM-1 / TpTta-COF MMMs after adding TpTta-COF nanoparticles was significantly improved, and successfully surpassed the Robeson upper limit (2008) of gas pairs CO2 / N2 and CO2 / CH4. When the filler TpTta-COF loading was 6wt%, the CO2 permeation flux of PIM-1 / TpTta-COF MMMs was the highest, 9534 Barrer, and the CO2 / N2 selectivity was 26.3. This gas separation performance is close to the 2019 Jansen / Mckeown separation upper limit.

[0071] Long-term operation stability is an important indicator in membrane separation technology. PIM-1 / TpTta-COF 6wt% MMMs were selected as representatives. The long-term stability of the modified membrane was studied for 3 days at a feed pressure of 3 bar and room temperature by using a CO2 / N2 mixed gas. Fig.10 As shown in Figure d, after 3 days of operation, the CO2 permeation flux remained at around 9456 Barrer, and the CO2 / N2 selectivity was 26.2, indicating that the interface between the filler TpTta-COF and the matrix PIM-1 was significantly stabilized due to the presence of hydrogen bonds. The excellent stability of MMMs provides a new method for capturing and separating CO2.

[0072] The present invention belongs to the key research and development plan of Hunan Province 2021GK2014, which is the research, development and application of separation membrane materials oriented to the deep treatment function of fluorine-containing wastewater.

[0073] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a mixed matrix membrane, characterized in that: The steps include: (1) Providing an intrinsic microporous polymer PIM-1; (2) subjecting 1,3,5-trialdehyde phloroglucinol and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to a microwave reaction in the presence of a catalyst to prepare a covalent framework polymer TpTta-COF having a β-ketoenamine structure; (3) PIM-1 and TpTta-COF were dispersed in a solution, and a PIM-1 / TpTta-COF mixed matrix membrane was prepared using a solution casting evaporation method with PIM-1 as the matrix and TpTta-COF as the loaded filler.

2. The method for preparing a mixed matrix membrane according to claim 1, characterized in that: The molar ratio of 1,3,5-trialdehyde phloroglucinol to 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added in step (2) is (0.95-1.05):

1.

3. The method for preparing a mixed matrix membrane according to claim 1 or 2, characterized in that: The catalyst in step (2) is HOAc, and the molar ratio of HOAc to 1,3,5-trialdehyde phloroglucinol is (20-25):

1.

4. The method for preparing a mixed matrix membrane according to claim 1 or 2, characterized in that: The microwave reaction temperature in step (2) is 80-150°C, the frequency is 10-100 GHz, and the reaction time is 10-30 min.

5. The method for preparing a mixed matrix membrane according to claim 1 or 2, characterized in that: The TpTta-COF prepared in step (2) is a nanorod with a diameter less than 30 nm and a length not exceeding 200 nm, and is a crystalline polymer material having a periodic hexagonal framework.

6. The method for preparing a mixed matrix membrane according to claim 1 or 2, characterized in that: The mass percentage of TpTta-COF in the PIM-1 / TpTta-COF mixed matrix membrane in step (3) is 2-8%.

7. A mixed matrix membrane, characterized in that The method is prepared by any one of claims 1 to 6.

8. Use of the mixed matrix membrane according to claim 7 in gas separation.

Citation Information

Patent Citations

  • Mixed matrix membranes incorporating microporous polymers as fillers

    CN102112203A

  • Polyethylene modified multilayer composite film for water treatment and preparation method thereof

    CN112387128A